Single-Laboratory Validation of Rapid and Easy DNA Strip for Porcine DNA Detection in Beef Meatballs. (23rd November 2019) - Riztyan,; Takasaki, Kazuto; Yamakoshi, Yukiko; Futo, Satoshi
Abstract: Detection of meat from an animal species is required to avoid misleading food labels to consumers. Recently, we developed an easy-to-use molecular detection method by combining isothermal amplification and a DNA strip, referred to as DNA Strip. Here, we report our single-laboratory validation of DNA Strip to detect porcine DNA in beef meatballs. Our results showed that DNA Strip could specifically amplify the target of porcine DNA, with detection limit to 0.01% admixture of pork in beef meatballs. DNA Strip method was also robust because the use of heat block and laboratory water bath showed no significant differences and were comparable to the reference instrument. DNA Strip can detect porcine DNA within ca 1 h, including DNA extraction, DNA amplification, and detection. These results suggest that DNA Strip is applicable because it is easy to use and capable of detecting pork in beef meatballs with a greater detection limit.